SPREADING THE ECONOMIC KNOWLEDGE INTO SMALL INDUSTRIAL REGIONS OF THE RUSSIAN FEDERATION IS A WAY OF INNOVATION DEVELOPMENT - Olga I. Mityakova; Elena A. Dubik (Статистика и экономика)
The article deals with a continuous integrated system of the professional training of specialists for industrial enterprises in small regions of Russia: school - higher school - enterprise. The system contributes to the development of human capital and production, integration and coordination of intellectual, scientific, technical and technological capacities, anchoring of well - educated young specialist at the enterprise, availability of educational resources, shortening the difference in the economic development of the regions.